Analisa Keputusan Pembelian Konsumen Dan Persepsi Harga Terhadap Kualitas Produk Starbucks Yang Dimediasi Kepuasan Konsumen - Harjono, Ardelianawati Putri; Rhomadhonis, Suci; Kristaung, Robert (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research is to explore how consumers' purchasing decisions and their views on price influence Starbucks product quality, with a focus on the role of consumer satisfaction as a link. This research involved conducting a survey in a specific area by distributing questionnaires to Starbucks customers. After the data was collected, analysis was carried out using the regression method to investigate the correlation between the observed variables. Based on research findings, it is concluded that consumer purchasing decisions have a positive effect on customer satisfaction levels. Apart from that, views on price also make a positive contribution to consumer satisfaction. Furthermore, customer satisfaction acts as a link between consumer purchasing decisions and price perceptions of Starbucks product quality. In simple terms, consumer purchasing decisions and views on price also influence consumer satisfaction, which then impacts consumer perceptions of the quality of Starbucks products. In conclusion, consumer purchasing decisions and price perceptions play an important role in shaping consumer satisfaction with the quality of Starbucks products. Starbucks management needs to pay attention to these factors in marketing and pricing strategies to increase consumer satisfaction and consumer perceptions of the quality of their products.